Implementation of Arabic Language Learning Media in Islamic Universities: Benefits and Problems - Mufidah, Isna; Khoiriyah, Siti; Ainiy, Nurul (Institut Agama Islam Negeri Palangka Raya, 2025)
Learning media plays a crucial role in facilitating effective teaching and learning activities. As instructional aids, media support educators in delivering material and enhancing student comprehension. In Arabic language learning, the four linguistic skills—Istima’ (listening), Kalam (speaking), Qira’ah (reading), and Kitabah (writing)—require diverse media tailored to their specific functions and objectives. This study explores the implementation of learning media in Arabic language education within Islamic higher education institutions, focusing on the benefits and challenges encountered. Employing a qualitative descriptive method, data were collected through observations, interviews, and documentation. The findings reveal that various types of media are utilized, including audio, visual, audio-visual, and interactive multimedia formats. While these media provide significant benefits in enhancing student engagement and comprehension, challenges such as resource limitations and adaptation issues persist. This study contributes to efforts aimed at optimizing the use of learning media to improve the quality of Arabic language education in Islamic higher education institutions.